Synthesis and characterization of Al2O3-SnO2 composite nanofibers by electrospinning for dye-sensitized solar cells - Ling, Jin Kiong (2019)
Materials engineering has been an inevitable part of technological advancements; many advanced technologies came in effect because of availability of new and high performing materials. This thesis investigates the structural, optical and electrical properties of a novel material, viz. a composite nanofiber containing amorphous Al2O3 and crystalline SnO2; properties of this composite has been benchmarked with pure nanofibers of amorphous Al2O3, crystalline SnO2, and Al-doped SnO2. Rationale of selection of these materials is the fact that Al2O3 is an insulator but offer high specific surface area whereas SnO2 is highly conducting but with compromised surface area – combining high specific surface area and high conductivity in one material would have potential impacts in nanoelectronics. For example, such materials are sought as photoanodes in dye-sensitized solar cells (DSSCs), which generated immense attention in clean energy research due to their capability of operating at dim light intensity. Six materials were prepared containing 5, 10, 25, and 50% of Al2O3 in SnO2 in addition to pure Al2O3 and SnO2 nanofibers by electrospinning technique. The as-spun polymeric fibrous cloths were calcined at 550 oC, which resulted in the crystallite –amorphous composite materials. The prepared samples were studied using Field Emission Scanning Electron Microscope, X-ray Diffraction, X-ray Photoelectron Spectroscopy, UV-Vis Spectrophotometer, Brunauer–Emmett–Teller (BET) surface analysis and Electrochemical Impedance Spectroscopy. Nanofiber structure was confirmed in all the samples. The XRD spectra showed no peak of Al2O3, indicating amorphous Al2O3 whereas SnO2 was fully crystallized. The absorption spectroscopy showed decrease in sample’s absorption and scattering coefficient indicating that higher ratio of Al2O3 in SnO2 is not suitable for the DSSCs application. Energy gap calculated from the absorption spectroscopy resulted in a narrowed energy gap when more Al2O3 was added into SnO2. The BET analysis showed an increase in sample’s surface area with increase in the Al2O3 content in SnO2 and electrochemical impedance spectroscopic analyses showed that the increase in surface area is at the expense of sample’s conductivity. The DSSCs were fabricated using the nanofibers developed here and characterized their photovoltaic properties using current – voltage measurements at AM 1.5 conditions; the cells showed improved performance for the 5-10% of Al2O3 doped in SnO2, with efficiency of 2% compared to SnO2 (~0.5%). Interestingly, the 1:1 SnO2/Al2O3 composite showed a conductivity similar to that of Al2O3; however, this composite when used as a photoanode showed orders of magnitude higher photovoltaic properties compared to that fabricated using pure Al2O3, due to the band bending effect at the nanofibers and cluster interface, facilitating the flow of electrons. This study opens up new opportunities in studying the structure – property correlations in amorphous – crystalline materials composites.